Nanotechnology-Enhanced Orthopaedic Surgery - Alexander Shao-Rong Pang; Zi Qiang Glen Liau; Jacob Yoong-Leong Oh; Dinesh Kumar Srinivasan (Journal of Nanotheranostics)
Nanomaterials hold significant promise for the future of orthopaedic implants due to their ability to mimic the nanoscale components of the bone, such as collagen fibrils and hydroxyapatite. Nanomaterials can regulate cell behaviour while offering mechanical strength and biocompatibility, making them ideal for bone repair and tissue regeneration. This comprehensive review explores the key existing and potential applications of nanotechnology in orthopaedics, including bone tissue engineering, drug delivery systems, systems combatting implant-related infections, and the surface preparation of implants to enhance osseointegration. These innovations are poised to revolutionise orthopaedic care by improving implant durability, reducing infection risks, and promoting bone regeneration to deliver personalised treatment and create better patient outcomes.